Assigning evidence to actionability: An introduction to variant interpretation in precision cancer medicine. Issue 6 (9th August 2021) - Horak, Peter; Leichsenring, Jonas; Goldschmid, Hannah; Kreutzfeldt, Simon; Kazdal, Daniel; Teleanu, Veronica; Endris, Volker; Gieldon, Laura; Allgäuer, Michael; Volckmar, Anna‐Lena; Dikow, Nicola; Renner, Marcus; et al.
Abstract: Modern concepts in precision cancer medicine are based on increasingly complex genomic analyses and require standardized criteria for the functional evaluation and reporting of detected genomic alterations in order to assess their clinical relevance. In this article, we propose and address the necessary steps in systematic variant evaluation consisting of bioinformatic analysis, functional annotation and clinical interpretation, focusing on the latter two aspects. We discuss the role and clinical application of current variant classification systems and point out their scope and limitations. Finally, we highlight the significance of the molecular tumor board as a platform for clinical decision‐making based on genomic analyses.